Carbon sequestration potential of a sal (Shorea robusta) dominated community forest in central Nepal - Ojha, Rujan; Sapkota, Jun; Kafle, Gandhiv (Journal of Agriculture and Natural Resources, 2025)
This study assessed the biomass and carbon stocks above and below ground in a community forest in central Nepal that is dominated by Sal (Shorea robusta). A basic random sample design with a 2% sampling intensity and 500 m² circular plots was used to gather field data from Block 1 of the Piple Pokhara Community Forest, Makawanpur District, between October 2021 and March 2022. Tree height and diameter at breast height (DBH) were measured, and standard allometric equations were used to determine biomass. A total of 78 individual trees were measured across the eight sample plots. With a mean height of 13.18 m and a mean DBH of 20.66 cm, the forest showed moderate structural variability. The average total biomass per tree was 315.63 kg, with mean above-ground and below-ground biomass of 263.03 kg and 52.61 kg, respectively. Above-ground components accounted for the highest share of the corresponding mean carbon stocks, which were 0.12 tons above-ground, 0.02 tons below-ground, and 0.15 tons overall per tree. Plot-to-plot variations in carbon stocks ranged from 0.11 to 0.20 tons per tree, primarily due to variations in tree size. The findings highlight the role of community forests in Nepal's efforts to mitigate climate change and account for carbon emissions. They show that the community forest serves as an efficient local carbon sink and that better forest management that focuses on stand structure could further enhance its carbon sequestration potential.